How to invent - Thring, M. W.; Laithwaite, E.R. ([London] : Macmillan Publishing Company, 1977)
The primary objective of this book is to give people who have a spark of creativity in them the possibility of using this spark to invent practical useful objects.
1. What is 'invention' and can it be taught? -- 2. Some historic inventions and inventors -- 3. What needs inventing? -- 4. The art of the inventor -- 5. Physical thinking -- 6. Engineering and nature study -- 7. Thinking with the hands -- 8. Teaching invention -- 9. Developing and patenting an invention -- 9. Developing and patenting an invention -- 10. Some of our inventions.
Includes index.
Keywords: INVENTIONS